Preparation and characterization of BN modified PA6/PC thermal conductive composites. Issue 3 (3rd July 2022) - He, Cong; Lin, Yi; Xiao, Chunguang; Lang, Feng; Li, Duxin
ABSTRACT: In this paper, BN was used for composite modification of the PA6/PC incompatible blends, and the effects of BN filling amount on thermal conductivity of PA6/PC/BN multiphase composites were systematically studied. Results indicated that compared with single-phase matrix composites, the two-phase matrix exhibited slightly better thermal conductivity under the same amount of BN. At the same time, the thermal conductivity of PA6/PC/BN gradually increased with the increase in BN content. When the BN content was 33.33 wt%, the thermal conductivity of PA6/PC/BN composite reached the maximum value of 0.953 W/(m·K), which was about 4.5 times of the matrix. In addition, the content of BN had a great influence on the melting crystallization behavior of the composite, and the addition of BN had a significant increase in the crystallization temperature of the materials.